2022
DOI: 10.3390/land11010077
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Water Use Efficiency: Is There Any Spatial Correlation between Different Regions?

Abstract: Affected by global climate change and water shortages, food security continues to be challenged. Improving agricultural water use efficiency is essential to guarantee food security. China has been suffering from water scarcity for a long time, and insufficient water supply in the agricultural sector has seriously threatened regional food security and sustainable development. This study adopted the super-efficiency slack-based model (SBM) to measure the provincial agricultural water use efficiency (AWUE). Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Some studies have analyzed the influencing factors of environmental pollution in the Yangtze River Economic Belt and confirmed the environmental Kuznets curve hypothesis, explaining the influence of economic growth by scale and structural effects by two important factors: industrial structure and population density (Wang et al, 2022). It is also argued that the degree of openness to the outside world and the level of information can improve the economic links between basins (Li et al, 2019), break the trade barriers of administrative divisions, and enhance the transfer of human, material, financial, and information technology between basins, which is an important driving force affecting the efficiency of water resources and its spatial network (Zhi et al, 2022). Some studies have also used systematic GMM model estimation with dynamic panels to conclude that the intensity of environmental regulations in cities along the middle and lower reaches of the Yellow River has a significant positive impact on improving the efficiency of water resources use, and that focusing on the quality of development of new urbanization is an important countermeasure to improve the efficiency of water resources use .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have analyzed the influencing factors of environmental pollution in the Yangtze River Economic Belt and confirmed the environmental Kuznets curve hypothesis, explaining the influence of economic growth by scale and structural effects by two important factors: industrial structure and population density (Wang et al, 2022). It is also argued that the degree of openness to the outside world and the level of information can improve the economic links between basins (Li et al, 2019), break the trade barriers of administrative divisions, and enhance the transfer of human, material, financial, and information technology between basins, which is an important driving force affecting the efficiency of water resources and its spatial network (Zhi et al, 2022). Some studies have also used systematic GMM model estimation with dynamic panels to conclude that the intensity of environmental regulations in cities along the middle and lower reaches of the Yellow River has a significant positive impact on improving the efficiency of water resources use, and that focusing on the quality of development of new urbanization is an important countermeasure to improve the efficiency of water resources use .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In reference to relevant scholars' research [1][2][3][4][5][6][7], it is found that the study of water resource efficiency issues are mostly from two perspectives: input and output to build an evaluation index system. From the input perspective, indicators are mostly constructed from equipment, labour and resources, while from the output perspective, indicators are selected from the economic and social dimensions to represent desired outputs, and in addition to economic and social outputs, there are also negative outputs that are not required by people, called non-desired outputs.…”
Section: Evaluation Indicator System Constructionmentioning
confidence: 99%
“…Thus, this article explores Biblioshiny for bibliometric analysis to assess the current literature on the evolution of studies on sustainable use of water in agriculture, identifying which of the literature perspectives have witnessed the most attention and where future research areas might be directed. Similar to our study, [40] covered sustainable agricultural water use research using the Scopus database, yet our article selection database is dissimilar, and our article identification queries and indicators are much broader. Although they identified top authors, articles, journals, and methodologies used within their survey, even so, the outcome of our study differs considerably.…”
Section: Introductionmentioning
confidence: 99%